Pengembangan Alat Rehabilitasi Smart Skeleton dengan Metode Neurodevelopmental Therapy dan Teknologi Exoskeleton bagi Penderita Cerebral Palsy - Arimbi, Anjaswari Resti (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
Cerebral palsy (CP) is a brain complex disorders that causes motoric disorders in children. Based on World Health Organization, more of 17 million people in the world diagnosed with CP. The prevalence rate of CP in the world reached 2 of 1.000 live birth. While the prevalence rate of CP in Indonesia reached 3 – 4 of 1.000 live birth. The rehabilitation principle of CP there is a basic methode namely Neurodevelopmental Therapy (NDT), which consists of three main principles. The method of this research is research and development (R&D) method. Which is divided into three stages, i.e. 1) literature study; 2) implementation; 3) testing. The test was carried out by measuring the Range of Motion (ROM) created by the servo motor and the current and frequency produced by the electrical stimulant. The results of this research are smart skeleton is able to apply three NDT principles. The smart skeleton manufacturing method is designed using braces, servo motors and electrical stimulants as the main components. The resulting Range of Motion is able to follow normal ROM and is capable of delivering a current of 0 – 101,6mA and a frequency of 0 – 91,7Hz. The conclusion of this research is smart skeleton has succeeded in developing innovative rehabilitation device for CP using NDT methods, servo motor based of arduino mega, and addition of an electrical stimulation.